Outcomes of autologous bone marrow mononuclear cell transplantation in decompensated liver cirrhosis - Bai, Yang-Qiu (Baishideng Publishing Group Inc, 2014)
AIM: To determine the long-term efficacy of autologous bone marrow mononuclear cells (BM-MNCs) transplantation in terms of improving liver function and reducing complications in patients with decompensated cirrhosis. METHODS: A total of 47 inpatients with decompensated liver cirrhosis were enrolled in this trial, including 32 patients undergoing a single BM-MNCs transplantation plus routine medical treatment, and 15 patients receiving medical treatment only as controls. Forty-three of 47 patients were infected with hepatitis B virus. Bone marrow of 80-100 mL was obtained from each patient and the BM-MNCs suspension was transfused into the liver via the hepatic artery. The efficacy of BM-MNCs transplantation was monitored during a 24-mo follow-up period. RESULTS: Liver function parameters in the two groups were observed at 1 mo after BM-MNCs transfusion. Prealbumin level was 118.3 ± 25.3 mg/L vs 101.4 ± 28.7 mg/L (P = 0.047); albumin level was 33.5 ± 3.6 g/L vs 30.3 ± 2.2 g/L (P = 0.002); total bilirubin 36.9 ± 9.7 mmol/L vs 45.6 ± 19.9 mmol/L (P = 0.048); prothrombin time 14.4 ± 2.3 s vs 15.9 ± 2.8 s (P = 0.046); prothrombin activity 84.3% ± 14.3% vs 74.4% ± 17.8% (P = 0.046); fibrinogen 2.28 ± 0.53 g/L vs 1.89 ± 0.44 g/L (P = 0.017); and platelet count 74.5 ± 15.7 × 10(9)/L vs 63.3 ± 15.7 × 10(9)/L (P = 0.027) in the treatment group and control group, respectively. Differences were statistically significant. The efficacy of BM-MNCs transplantation lasted 3-12 mo as compared with the control group. Serious complications such as hepatic encephalopathy and spontaneous bacterial peritonitis were also significantly reduced in BM-MNCs transfused patients compared with the controls. However, these improvements disappeared 24 mo after transplantation. CONCLUSION: BM-MNCs transplantation is safe and effective in patients with decompensated cirrhosis. It also decreases the incidence of serious complications.